1995
DOI: 10.1002/j.1460-2075.1995.tb00301.x
|View full text |Cite
|
Sign up to set email alerts
|

E-cadherin is a tumour/invasion suppressor gene mutated in human lobular breast cancers.

Abstract: Compelling experimental evidence exists for a potent invasion suppressor role of the cell‐cell adhesion molecule E‐cadherin. In addition, a tumour suppressor effect has been suggested for E‐cadherin. In human cancers, partial or complete loss of E‐cadherin expression correlates with malignancy. To investigate the molecular basis for this altered expression we developed a comprehensive PCR/SSCP mutation screen for the human E‐cadherin gene. For 49 breast cancer patients the occurrence of tumour‐specific mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
563
8
6

Year Published

1997
1997
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 710 publications
(594 citation statements)
references
References 36 publications
17
563
8
6
Order By: Relevance
“…Since some zinc fingers also mediate protein-protein interaction, CM-2 could represent a functional domain of PCDH10 interacting with other cellular proteins. One major mechanism for cadherins in tumor suppression is through the Wnt/b-catenin/Tcf signaling pathway (Angst et al, 2001), an important gatekeeper of tumorigenesis (Berx et al, 1995;Perl et al, 1998). However, protocadherins including PCDH10 do not bind to b-catenin (Frank and Kemler, 2002), so whether they can also interfere with the Wnt signaling pathway is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since some zinc fingers also mediate protein-protein interaction, CM-2 could represent a functional domain of PCDH10 interacting with other cellular proteins. One major mechanism for cadherins in tumor suppression is through the Wnt/b-catenin/Tcf signaling pathway (Angst et al, 2001), an important gatekeeper of tumorigenesis (Berx et al, 1995;Perl et al, 1998). However, protocadherins including PCDH10 do not bind to b-catenin (Frank and Kemler, 2002), so whether they can also interfere with the Wnt signaling pathway is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of cadherins or their functional alterations have been frequently observed in human malignancies, which promotes tumor cell invasion and metastasis (Berx et al, 1995;Perl et al, 1998), suggesting that at least some cadherins can act as tumor suppressor genes (TSG). Mutations of E-cadherin (CDH1) have been reported in familial and sporadic gastric cancers and other tumors (Risinger et al, 1994;Berx et al, 1995;Guilford et al, 1998). CDH13 also has truncating mutations in tumors which lead to the deletion of transmembrane and cytoplasmic regions and disruption of its tumor suppression functions (Lee, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Reduced expression of E-cadherin has been reported in invasive ductal carcinoma whereas lobular carcinoma in situ and invasive lobular carcinoma show complete loss of the protein. [6][7][8][9][10][11][12][13][14][15][16] A report on invasive lobular carcinomas with adjacent lobular carcinoma in situ demonstrated not only loss of Ecadherin expression but also the simultaneous loss of beta-, gamma-and alpha-catenin protein expression. 15 More recently, Sarrio et al 17 demonstrated that the loss of E-cadherin along with the cytoplasmic localization of p120-catenin characterizes lobular breast cancers and suggested that p120-catenin plays a role in mediating the oncogenic effects of Ecadherin loss in these cancers.…”
mentioning
confidence: 99%
“…Mutations have been detected in invasive lobular carcinoma and lobular carcinoma in situ with adjacent invasive, 6,[11][12][13][14][15][16] and the loss of chromosome 16q was detected in solitary in situ and synchronous in situ/invasive lesions. 1,18 These investigations of lobular carcinoma and Ecadherin have provided some evidence that in situ lobular carcinoma may be not only a risk indicator but also a precursor lesion to invasive carcinoma.…”
mentioning
confidence: 99%
“…2 Studies in cancer cell lines have shown that changes in the structure or in the expression of the components of the E-cadherin/␤-catenin complex result in the suppression of cell-cell adhesion and in the expression of an invasive phenotype. [3][4][5][6][7][8] In cancer, the maintenance of the epithelia is lost and dissociation of cells is associated with metastatic dissemination. This phenomenon can occur through a decrease in the expression level of E-cadherin and, regarding colon cancer, such decrease has been related to the tumor grade and clinical outcome.…”
mentioning
confidence: 99%